Time Series Properties of the German Monthly Production Index - Gebhard Flaig (Center for Economic Studies and ifo Institute (CESifo), 2003)
The production index is an important indicator for assessing the cyclical state of the economy. Unfortunately, the monthly time series is contaminated by many noisy components like seasonal variations, calendar and vacation effects. Only part of those nuisance components are explicitly considered in the seasonal adjustment procedures used by statistical agencies. In this paper, we propose a more flexible specification for the seasonal and working day effects and introduce an indicator for the summer vacations effect. We allow for time-varying parameters and show that the resulting Unobserved Components Model delivers more reliable results for the adjusted series.
Keywords: 330; production index; seasonal adjustment; working day effect; business cycles; unobserved components models